Co-registration of optical coherence tomography and X-ray angiography in percutaneous coronary intervention. The Does Optical Coherence Tomography Optimize Revascularization (DOCTOR) fusion study. (1st March 2015) - Hebsgaard, Lasse; Nielsen, Troels Munck; Tu, Shengxian; Krusell, Lars Romer; Maeng, Michael; Veien, Karsten Tange; Raungaard, Bent; Terkelsen, Christian Juhl; Kaltoft, Anne; Reiber, Johan H.C.; Lassen, Jens Flensted; Christiansen, Evald Høj; et al.
Abstract: Background: Intracoronary imaging provides accurate lesion delineation and precise measurements for sizing and positioning of coronary stents. During percutaneous coronary intervention (PCI), it may be challenging to identify corresponding segments between intracoronary imaging and angiography. Computer based online co-registration may aid the target segment identification. Methods: The DOCTOR fusion study was a prospective, single arm, observational study including patients admitted for elective PCI. Optical coherence tomography (OCT) was acquired pre-stent implantation for sizing of stents. The operator subsequently indicated on the angiogram the target area as identified by OCT. Computer based co-registration was performed on-line immediately after pre-stent acquisition to assess feasibility. The cumulated numerical difference between operator based, and computer based co-registration was assessed as the "Operator Registration Error". The operator implanted the stent blind to the co-registrated angiogram. The difference between the co-registered stent border positions and the actual stent deployment border positions was the "Geographic Miss Distance". Results: Twenty-two patients were included in the study. Two patients were excluded due to missing pre or post-OCT acquisitions. Online co-registration pre-stenting was successful in all analyzed cases. The mean "Operator Registration Error" was 5.4 ± 3.5 mm. The mean "Geographic Miss Distance" was 5.4 ± 2.6 mm. Without access to the computer-based co-registration, segments of the target lesion indicated on OCT were left uncovered by stent in 14 patients (70%). Conclusion: Computer based online co-registration of OCT and angiography is feasible. Frequent inaccuracies in operator based registration indicate that computer aided co-registration may reduce errors in corresponding OCT findings to the angiogram.